Effects of fermented cottonseed meal on growth performance, serum biochemical parameters, immune functions, antioxidative abilities, and cecal microflora in broilers. Issue 4 (4th July 2017) - Wang, Yongwei; Deng, Qingqing; Song, Dan; Wang, Weiwei; Zhou, Hang; Wang, Li; Li, Aike
ABSTRACT: The study was to investigate the effects of fermented cottonseed meal (FCSM) on growth performance, serum biochemical parameters, immune functions, antioxidative abilities, and cecal microflora in broilers. The cottonseed meal (CSM) was fermented with Bacillus subtilis ST-141 and Saccharomycetes N5 . Hundred and twenty-eight one-day-old male Arbor Acres broilers were randomly divided into four groups: a corn-soybean meal (SBM) basal diet, and three experimental diets (CSM, FCSM-1, and FCSM-2) in which the control diet was supplemented with CSM or FCSM to partially replace SBM. Results showed that the fermentation process can effectively decrease free gossypol level, and increase acid-soluble protein level in CSM. The levels of immunoglobulin, biochemical parameters, antioxidative abilities in serum or liver tissue, and Lactobacilli and total anaerobic bacteria counts in ceca digesta of birds fed FCSM-1 were improved compared with birds fed CSM or FCSM-2 on days 21 and 42. So FCSM can be effectively applied in broiler diets.